Continuous-Flow Photochemical Isomerization of Humulones to Isohumulones - Bruce C. Hamper; Bradley Gallow; Gregory Giovine; Trevor Smith (Molecules)
Humulones are a family of homolog natural products obtained from the strobiles of humulus lupulus, or hops plants. Structurally, they consist of substituted phloroglucinols with two isoprenyl side chains, a carbonyl group and a quaternary ring carbon substituted with a hydroxyl group. The three most prominent homologs are n-, co- and ad-humulone, containing isobutyl, isopropyl and secbutyl ketone groups, respectively. When solutions of humulones are exposed to UV light, they undergo stereoselective isomerization to the five-membered ring trans-isohumulones. A photoreactor was assembled from strip LEDs in close contact with UV-transparent tubing. This reactor allowed continuous-flow chemical synthesis of the isohumulones. The yield, conversion and product throughput are compared for the humulones, using LEDs emitting white, blue and ultraviolet light (visible, 400 nm, and 365 nm, respectively). Using an optimized continuous-flow reactor, a throughput of 0.43 g/h was obtained for trans-n-isohumulone.